PROPER NOUN AND ITS INTERPRETATION IN LINGUISTICS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article is devoted to the study of phraseological units with proper nouns. The article also describes in detail some phraseological units with semantic designations and components, moreover, examples are given on different contexts. A proper noun in the phraseological unit performs both special onomastic and general linguistic functions. The dominant role is played by the cultural-informative function, which is confirmed by the richness of connotations of this group of names, their polyconnotativity, word-formation and phraseformation activity.